Comparing LAMA with LABA and LTRA as add-on therapies in primary care asthma management - Kaplan, Alan (NPJ Prim Care Respir Med, 2020)
The Global Initiative for Asthma recommends a stepwise approach to adjust asthma treatment to the needs of individual patients; inhaled corticosteroids (ICS) remain the core pharmacological treatment. However, many patients remain poorly controlled, and evidence-based algorithms to decide on the best order and rationale for add-on therapies are lacking. We explore the challenges of asthma management in primary care and review outcomes from randomised controlled trials and meta-analyses comparing the long-acting muscarinic antagonist (LAMA) tiotropium with long-acting β(2)-agonists (LABAs) or leukotriene receptor antagonists (LTRAs) as add-on to ICS in patients with asthma. In adults, LAMAs and LABAs provide a greater improvement in lung function than LTRAs as add-on to ICS. In children, results were positive and comparable between therapies, but data are scarce. This information could aid decision-making in primary care, supporting the use of add-on therapy to ICS to help improve lung function, control asthma symptoms and prevent exacerbations.